The Determinants of Home Bias in Stock Portfolio: An Emerging and Developed Markets Study - Chniguir, Mounira; Kefi, Mohamed Karim; Henchiri, Jamel Eddine (International Journal of Economics and Financial Issues, 2017)
The objective of this paper is to measure the degree of Home Bias within holdings portfolio and to identify their determining factors. By following literature and an international CAPM, we have chosen quite a number of susceptible factors that impact Home Bias. This model is, hence, estimated for 20 countries, with cross-section econometrics, between 2008 and 2013. Our results show that all countries have recorded a high level of Home bias in their holdings portfolio. After that, we test if the Home Bias of the emerging markets and that of the developed markets react differently to the determining factors. The volatility of the exchange rate is statistically significant with emerging markets, while it is hardly remarkable for the developed countries. Co-variance, size, distance, language, legal framework and foreign organization stocks prevents American investors to invest abroad. Keywords: International portfolio, Home Bias, exchange rate, emerging market, CAPM JEL Classifications: F31, G11